Challenges in Assessing Outcomes among Infants of Pregnant HIV-Positive Women Receiving ART in Uganda. (7th December 2017) - Castelnuovo, Barbara; Mubiru, Frank; Kalule, Ivan; Nakalema, Shadia; Kiragga, Agnes
Abstract : Since 2012, the WHO recommends lifelong ART with TDF+FTC/3TC+EFV for all HIV-positive pregnant and breastfeeding women (Option B-plus). In this analysis we describe the proportion of early and late transmission in mothers with high retention in Kampala, Uganda. We included 700 pregnant women from January 2012 to August 2014 with a follow-up extended to August 2016; the median age was 31 years (IQR: 26–35), 36.3% in WHO stage 3/4; median CD4 count was 447 cells/ μ L (IQR: 301–651) and 73.3% were already on ART for a median time of 28 (IQR: 10–57) months; 52% infants were male and median weight was 3.2 Kg (IQR: 2.5–3.5). Five hundred and sixty-five (80.7%) infants had at least one test for HIV; 22 (3.1%) infants died, all with unknown serostatus; 3 tested positive at week 6 and one additional at months 12 and 18. Two of the mothers of the 4 HIV-positive infants were ART-naïve at the time of pregnancy. We report very low documented HIV transmission comparable with those reported in clinical trials settings; however, demonstrating the efficacy of Option B-plus in terms of averted transmission in routine settings is challenging since high proportion of infants do not have documented HIV tests.